The Impact of Educational Service Quality on Student Satisfaction in Samarinda’s Higher Education Institutions - Marsuq Marsuq (Newinera Publisher, 2026)
This study examines the effect of educational service quality on student satisfaction in higher education institutions in Samarinda, Indonesia. Using a quantitative explanatory design, the study focused on five dimensions of educational service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. Data were collected from 313 undergraduate students from public and private higher education institutions in Samarinda through a structured questionnaire using a five point Likert scale. The data were analyzed using multiple linear regression to determine the partial and simultaneous effects of service quality dimensions on student satisfaction. The findings show that tangibles, reliability, responsiveness, assurance, and empathy have positive and significant effects on student satisfaction at the 0.05 significance level. Among these dimensions, empathy has the strongest influence, followed by responsiveness and reliability, indicating that students place high value on personal attention, responsive services, and consistent service delivery. The model explains 61.1 percent of the variance in student satisfaction, suggesting that educational service quality is an important determinant of students’ evaluative perceptions of their institutional experience. These findings highlight the need for higher education institutions to strengthen student centered service practices, particularly by improving relational quality, administrative responsiveness, and institutional reliability. The study contributes to educational management by emphasizing that student satisfaction is shaped not only by physical facilities but also by the quality of interaction between students and institutional service providers.